2008
DOI: 10.21236/ada479715
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Graphically: Connecting Vision and Cognition during Graph Comprehension

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
(21 reference statements)
1
19
0
Order By: Relevance
“…Similarly, Carpenter and Shah (1998) identified different stages of graph comprehension by analysing gaze durations spent on different parts of statistical graphs while participants answered interpretive questions (see also Shah & Carpenter, 1995;Shah, Hegarty, & Mayer, 1999). More recently, Renshaw, Finlay, Tyfa, and Ward (2004) have used eye tracking to evaluate the benefits of different graphical representations of information (see also Purchase, Carrington, & Allder, 2002), and Ratwani, Trafton, and Boehm-Davis (2008) have investigated search, reasoning and integration processes during comprehension of colour-coded map-like graphs. Because eye tracking-combined with proper experimentation-provides a moment-by-moment record of a reader's deployment of attention, it is particularly suited to reveal the temporal structure of comprehension of hierarchical graphs.…”
Section: Investigating Graph Comprehension Using Eye-tracking Techniquesmentioning
confidence: 99%
“…Similarly, Carpenter and Shah (1998) identified different stages of graph comprehension by analysing gaze durations spent on different parts of statistical graphs while participants answered interpretive questions (see also Shah & Carpenter, 1995;Shah, Hegarty, & Mayer, 1999). More recently, Renshaw, Finlay, Tyfa, and Ward (2004) have used eye tracking to evaluate the benefits of different graphical representations of information (see also Purchase, Carrington, & Allder, 2002), and Ratwani, Trafton, and Boehm-Davis (2008) have investigated search, reasoning and integration processes during comprehension of colour-coded map-like graphs. Because eye tracking-combined with proper experimentation-provides a moment-by-moment record of a reader's deployment of attention, it is particularly suited to reveal the temporal structure of comprehension of hierarchical graphs.…”
Section: Investigating Graph Comprehension Using Eye-tracking Techniquesmentioning
confidence: 99%
“…Studies examining eye movement data for different kinds of graphs have demonstrated that the processing of more complex and difficult graphs is associated with more and longer viewing of the graph. 16,17 As all 3 graphs included identical information depicted in the same way, except for shape, it was expected that differences in the eye movement data would be caused by the ease of interpretation of the shape. A shape was therefore considered more efficient than the others when the viewers needed less time and fewer gazes to process the graph.…”
Section: Data Collectionmentioning
confidence: 99%
“…Grant and Spivey (2003) have shown that guiding visual attention can improve diagram-based problem solving. More recently, Peebles and Cheng (2003), Renshaw, Finlay, Tyfa, and Ward (2004), Huang (2007) and Acarturk, Habel, Cagiltay, and Alacam (2008) have used eye tracking to evaluate the benefits of different graphical representations of information, and Ratwani, Trafton, and Boehm-Davis (2008) have investigated search, reasoning and integration processes during comprehension of so-called choropleth graphs (spatial colour-coded graphs). There are several possibilities of how readers extract and process graphical information.…”
Section: A Sequential Eye-movement Model Of Graph Processingmentioning
confidence: 99%